Rationally Designed Anti‐Glare Panel Arrays as Highway Wind Energy Harvester. (3rd February 2023) - Su, Erming; Li, Hao; Zhang, Jiabin; Xu, Zijie; Chen, Baodong; Cao, Leo N.Y.; Wang, Zhong Lin
Abstract: The anti‐glare panels along highways can block the dazzling lights of opposing vehicles at night, playing an important role in the highway safety. Inspired by the highway anti‐glare panels, wind energy harvesting triboelectric nanogenerator (AG‐TENG) arrays to properly capture energy from highway moving vehicles is developed. A single AG‐TENG installation module can achieve a high power density of 0.2 Wm −2 at a wind speed of 3 m s −1 . This wind speed is too low to drive conventional wind energy harvesting equipment. The performance of the AG‐TENG shows no degradation after 80 h of continuous operation (1 440 000 times). Thus, with the rational consideration and features, the system can generate enough power to drive internet of things (IoT) devices and environmental sensors, as well as offer wireless alarming and radio frequency identification vehicle monitoring. This study provides a promising strategy to properly harvest wind energy on highways using existing infrastructures under the condition of even no natural wind, showing broad application prospects in distributed environmental monitoring, intelligent highways, and the IoT. Abstract : To properly capture energy from highway moving vehicles, wind energy harvesting triboelectric nanogenerator arrays based on highway anti‐glare panels are developed. A single installation module can achieve a high power density of 0.2 Wm −2 at a wind speed of 3 m s −1 . The device shows no performance degradation after 80 h of continuous operation (1 440 000 times).